AN EMPIRICAL STUDY OF PUBLIC SPEAKING SKILLS: CHALLENGES AND COPING STRATEGIES AMONG UZBEK EFL STUDENTS - Urinova, Urazgul (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
The purpose of this empirical study is to investigate the public speaking competency of Uzbek students of English as a foreign language. The study focuses on the difficulties that these students face and the coping mechanisms that they use. Uzbekistan State World Languages University (UzSWLU) in Tashkent, Andijan State Institute of Foreign Languages, Andijan State University, and Denau Institute of Entrepreneurship and Pedagogy in Surkhandarya were the three universities that participated in the study that yielded the data. The survey was administered to a total of 215 students. The findings indicate that students confront a variety of obstacles, including those that are psychological (such as speech anxiety, fear of unfavorable judgment, and low confidence), linguistic (such as limited vocabulary, issues with pronunciation, and a lack of fluency), and environmental (such as teacher-centered techniques and insufficient practice chances). Rehearsal, script preparation, feedback from peers and teachers, mirror practice, recording, and involvement in debate clubs are some of the coping techniques that students have reported using. On top of that, students have indicated that they have a significant preference for technology-based solutions like as feedback systems driven by artificial intelligence, mobile applications, and virtual speaking spaces. Through crossanalysis with foreign literature, both similarities and differences that are peculiar to the setting are brought to light. This study makes a contribution to the understanding of English as a Foreign Language (EFL) public speaking competence in a local context. It provides a classification of challenges and strategies, and it offers practical recommendations for universities to incorporate learner-centered, technology-enhanced, and practice-oriented methods in order to strengthen students’ public speaking skills.
Keywords: public speaking competence; EFL students; speaking anxiety; coping strategies; learner-centered; teacher-centred